2012
DOI: 10.1073/pnas.1112848109
|View full text |Cite
|
Sign up to set email alerts
|

Class III PI3K Vps34 plays an essential role in autophagy and in heart and liver function

Abstract: A critical regulator of autophagy is the Class III PI3K Vps34 (also called PIK3C3). Although Vps34 is known to play an essential role in autophagy in yeast, its role in mammals remains elusive. To elucidate the physiological function of Vps34 and to determine its precise role in autophagy, we have generated Vps34 f/f mice, in which expression of Cre recombinase results in a deletion of exon 4 of Vps34 and a frame shift causing a deletion of 755 of the 887 amino acids of Vps34. Acute ablation of Vps34 in MEFs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
311
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(344 citation statements)
references
References 43 publications
33
311
0
Order By: Relevance
“…116 In this model, PIK3C3 is part of the MTOR complex; amino acids stimulate an elevation in the intracellular Ca 2C level and Ca 2C -CALM/calmodulin binding, which increases PIK3C3 activity; consequently, PtdIns3Ps produced by PIK3C3 activate MTOR by replacing FKBP8/FKBP38 with RHEB. 116 This model is consistent with earlier studies showing that PIK3C3 is required for MTOR-RPS6KB1 signaling activity, 117,118 and is supported by the evidence that amino acid restimulation of MTOR activity is impaired in Pik3c3 KO MEFs 111 and MTOR activity is remarkably ablated in Pik3c3 KO embryos. 110 However, several issues are still under dispute concerning the amino acid-Ca 2C -CALM-PIK3C3-MTOR signaling model.…”
Section: Regulation Of Autophagy By Pik3c3 Via Formation Of Protein Csupporting
confidence: 80%
See 3 more Smart Citations
“…116 In this model, PIK3C3 is part of the MTOR complex; amino acids stimulate an elevation in the intracellular Ca 2C level and Ca 2C -CALM/calmodulin binding, which increases PIK3C3 activity; consequently, PtdIns3Ps produced by PIK3C3 activate MTOR by replacing FKBP8/FKBP38 with RHEB. 116 This model is consistent with earlier studies showing that PIK3C3 is required for MTOR-RPS6KB1 signaling activity, 117,118 and is supported by the evidence that amino acid restimulation of MTOR activity is impaired in Pik3c3 KO MEFs 111 and MTOR activity is remarkably ablated in Pik3c3 KO embryos. 110 However, several issues are still under dispute concerning the amino acid-Ca 2C -CALM-PIK3C3-MTOR signaling model.…”
Section: Regulation Of Autophagy By Pik3c3 Via Formation Of Protein Csupporting
confidence: 80%
“…167,168 However, studies from several Pik3c3 knockout animal models suggest that PtdIns3P generation and autophagic function rely predominantly on PIK3C3 activity. 111,169,170 The question of whether class III PtdIns3K is the exclusive kinase responsible for PtdIns3P generation during autophagy remained unsolved until a recent study by Devereaux et al revealed an alternative source of PtdIns3P in Pik3c3 knockout MEFs. 171 In Pik3c3 KO MEFs, it is surprising that PtdIns3P is still detectable using a higher affinity PtdIns3P probe and the PtdIns3P-binding protein WIPI1, and autophagosomes are still observed under starvation conditions; class II PI3K was confirmed as another contributor to the PtdIns3P pool during autophagy, and depletion of class II PI3K further decreases autophagic flux, which is inhibited by Pik3c3 deletion.…”
Section: Regulation Of Autophagy By Pik3c3 Via Other Interacting Partmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that the consequences of LAMP2 deficiency (in Lamp2 heterozygous null mice) on global autophagic flux are only unmasked in the presence of a stressor such as fasting, which rapidly stimulates formation of autophagosomes, which are thereafter not processed efficiently, due to impaired autophagosome-lysosome fusion. Therefore, Lamp2 heterozygous null mice are well suited as a model system to evaluate the effects of impaired myocardial lysosome function and consequently impaired autophagy specifically under stress; as they do not display the disadvantages observed in other model systems employed to study the effects of impaired autophagy-lysosomal machinery, namely presence of cardiomyopathy in the unstressed state (as in mice with cardiac myocyte specific or germline ablation of proteins essential for autophagosome formation, ATG5, ATG7, and PIK3C3; 14,15,33,34 and in models of lysosomal dysfunction [reviewed in ref. 35]); or the paradoxical effects on autophagy observed with haploinsufficiency of BECN1.…”
Section: Fasting-refeeding Cycles Modulate Myocardial Autophagymentioning
confidence: 99%